Comparative Study of the Chemical Composition Disparities Between Fast-twitch and Slow-twitch Muscles in Marine Teleost Fishes - Huan WANG; Shufang LIU (Progress in Fishery Sciences)
Skeletal muscle contraction, which generates movement by pulling on the internal skeleton, is a distinctive mode of movement in vertebrates. Renowned for its flexibility, diversity, and efficiency, this mode of movement is significant for the individual survival and reproductive success of animals. Being the most ancient vertebrates, fish inhabit aquatic environments, where their skeletal muscles serve as structural and locomotor organs and as a crucial source of high-quality protein for human consumption. Based on the contraction characteristics, the skeletal muscles in teleost fishes are primarily categorized into fast-twitch and slow-twitch muscles, which play distinct roles, supporting burst swimming and prolonged endurance swimming, respectively. Preliminary analyses have been conducted on the structural, metabolic, and functional differences between the fast-twitch and slow-twitch muscles in fish at histological, enzymatic activity, and molecular regulatory levels. Proteins, amino acids, fat, fatty acids, and minerals constitute the material basis for the swimming function of fish skeletal muscles, providing a more intuitive and accurate reflection of the distinct physiological characteristics of fast-twitch and slow-twitch muscles. However, reported research on the comparative analysis of the material constituents comprising fast-twitch and slow-twitch muscles is scarce. To comprehend the chemical composition characteristics and elucidate the material basis for the functional differences between fast-twitch and slow-twitch muscles, this study used biochemical analysis to determine the chemical components of the two muscle types in Pseudocaranx dentex and Liza haematocheila. We integrated data from the literature on tuna, including Thunnus tonggol, T. albacares, Auxis rochei, A. thazard, Euthynnus affinis, and Katsuwonus pelamisi. These fishes have different swimming habits, which can provide a more comprehensive perspective on the differences between fast-twitch and slow-twitch muscles. First, the fast-twitch muscles exhibited a substantial enrichment in protein and 12 types of amino acids, particularly histidine. Notably, histidine is pivotal as a proton-buffering substance and for maintaining pH stability. The relative content difference of histidine was pronounced, ranging from 1.22 to 3.83 times higher in fast-twitch muscles than in slow-twitch muscles. Regarding the amino acid compositions, fast-twitch and slow-twitch muscles displayed similarities, with essential amino acids constituting approximately 40% of the total amino acid content. Glutamate and aspartate were the predominant amino acids, playing essential roles in eliminating ammonia during exercise and serving as crucial energy substrates for muscle function. Lysine and leucine, the two essential amino acids with the highest content, were instrumental in ketone body formation, glucose metabolism, and fat metabolism, and provided an essential energy supply. Further analysis of the fat content and fatty acid composition revealed intriguing differences. Slow-twitch muscles exhibited significantly higher levels of fat and each fatty acid than their fast-twitch counterparts. The aerobic oxidation metabolism of fatty acids was characterized by a prolonged energy supply duration and substantial ATP generation. This unique metabolic profile suggests that slow-twitch muscles rely on fatty acids as their primary energy substrate during swimming for extended periods. Examining the fatty acid composition in detail, the proportion of saturated fatty acids (SFA) was higher in slow-twitch muscles, whereas fast-twitch muscles had a higher proportion of polyunsaturated fatty acids (PUFA). This divergence could be attributed to the specific requirements of each muscle type. Slow-twitch muscles, engaged in long-distance movements, necessitate more SFA and monounsaturated fatty acids (MUFA) for oxidative energy supply. Conversely, fast-twitch muscles, responsible for burst swimming, require more PUFA to maintain the structural integrity and functionality of cell membranes. The main fatty acid composition types of SFA, PUFA, and MUFA in the fast-twitch and slow-twitch muscles are the same. C16:0, C18:0, and C14:0 were the main SFA types. C18:1 and C16:1 were the main MUFA types. C22:6n3 and C20:5n3 were the main PUFA types. Finally, the mineral element analysis revealed that slow-twitch muscles possess higher iron and zinc concentrations, which are critical in oxygen transportation and catalyzation of oxidation processes. The potassium, magnesium, and calcium contents showed no significant correlation with muscle types. Potassium was identified as the most abundant constant element, magnesium exhibited minimal content fluctuation across diverse species, and calcium was the most abundant metallic element. In summary, our comprehensive investigation into the chemical composition of fast-twitch and slow-twitch muscles in marine teleost fishes uncovered significant distinctions in proteins, amino acids, fats, fatty acids, and mineral elements. These differences form the foundation for executing diverse swimming functions, shedding light on the intricate interplay between muscle composition and swimming performance in teleost fishes.